Jednostki samorządu terytorialnego jako beneficjent środków z Unii Europejskiej - Wasylik, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents questions related to the system of funding the activities of territorial self-government in relation to the absorption of the means coming from the European Union. The study mentions some problems connected with the importance of the funds for territorial self-government in the present-day period of programming, i.e. between 2004 and 2006. It also pays attention to some new solutions which should eliminate or weaken existing limitations of financial independence of territorial self-governments. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 310-319